Elastic Deformation and Elastic Wave Velocity for Cubic Metal and Binary Interstitial Alloy’s Thin Films at Different Temperatures, Pressures, Interstitial Atomic Concentrations and Film Thicknesses - Quang Hoc, Nguyen; Dat, Hua Xuan; Hang, Phan Minh; Viet, Le Hong; Quang Tuan, Doan; Si Gia Khoa, Quach (VNU Journal of Science: Mathematics - Physics, 2024)
The theory of elastic deformation and elastic wave for cubic metal and binary interstitial alloy’s thin films is builded by a statistical moment method (SMM). The obtained results have been applied to perform numerical calculations for W, Au, WSi and AuSi materials. Some SMM calculations for W, Au are compared with  experiments and other calculation methods. Other SMM calculations are new and predict experimental results.